The Development of Syllabus and Lesson Plan Based on English for Occupational Purposes - Sudipa, Nengah (International Journal of Psychosocial Rehabilitation, 2020)
English Language Courses taught to students in addition to the English language study program are in the form of English for Professionals (EOP) which can support students’ knowledge of the fields of science in their chosen study program. Thus, the preparation of syllabus and teaching material in English courses must be in accordance with the needs of students in the study program taught. In the Hospitality Management Study Program at the International Bali Tourism Institute, the use of syllabus in English courses in the 5th semester is still general, while English language learning will be used to support and create quality graduates who are able to compete in the workforce, especially those who need skills in English. The source of the data in this study came from the questionnaire. The process of data retrieval and preparation of research instruments are carried out in several stages, namely the needs analysis phase, product design phase, design validation stage, design revision stage, product testing phase.